2004
DOI: 10.1016/j.ejcts.2004.07.034
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of autologous ?blood patch? pleurodesis for persistent air leak after pulmonary resection

Abstract: In our experience a single injection of 50 ml of blood is sufficient to seal persistent air leaks in less than 48 h. Although highly effective, the autologous blood patch pleurodesis technique should not be used in patients with incomplete lung re-expansion or positive pleural fluid culture to minimize the risk of empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 12 publications
3
93
1
Order By: Relevance
“…Prior reports 19 have demonstrated upto 28% (3/28) rates of empyema and nearly 20% (2/11) rates of fever. 8 Three of our 76 (4%) developed pleural infection which although significant is much smaller complication rate than previously reported. We followed an absolute adherence to the contraindications and made the effort to rule out pre-existing infection.…”
Section: -200mlcontrasting
confidence: 44%
See 2 more Smart Citations
“…Prior reports 19 have demonstrated upto 28% (3/28) rates of empyema and nearly 20% (2/11) rates of fever. 8 Three of our 76 (4%) developed pleural infection which although significant is much smaller complication rate than previously reported. We followed an absolute adherence to the contraindications and made the effort to rule out pre-existing infection.…”
Section: -200mlcontrasting
confidence: 44%
“…This device not only connected the chest tube to the drainage system but also provided an extra port with a cap which was used to introduce the blood into the chest in a sterile fashion without having to make a needle stick hole in the chest tube itself or having to even temporarily disconnect the tube from the drainage pipe which has been described by others. 8 The drainage tube itself was also lengthened with the addition of another two meter tubing. This was done to allow adequate length for the tube be looped over an Intravenous (IV) stand.…”
Section: Technique Of Abpmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small observational studies have demonstrated the efficacy and safety of autologous blood in treating post-operative prolonged air leak (108)(109)(110). In these studies, patients with prolonged air leak (>5-10 days) after undergoing a variety of operations (lobectomy, wedge resection, bullectomy, lung volume reduction or decortication) were treated with 1-2 injections of autologous blood pleurodesis with resolution of air leak in all patients within 48 hours of therapy.…”
Section: Bedside Pleurodesismentioning
confidence: 99%
“…A variety of agents have been described for this purpose, including silver nitrate(100), quinacrine(101), minocycline(102), tetracycline (103), doxycycline(104), erythromycin (105), bleomycin (106), iodopovidone(107), talc powder (14) and autologous blood (108)(109)(110)(111). Be that as it may, contemporary literature has mainly focused on autologous blood for treatment of persistent post-operative air leaks, so the utility of the other agents for this clinical context are not as well known.…”
Section: Bedside Pleurodesismentioning
confidence: 99%